(untitled) (Research, Society and Development, 2021)
This study presents reflections on the formation of critical sense in the teaching and learning process, as a way to contribute to the change of behavior and attitudes towards contemporary issues and dilemmas in overcoming common sense. Methodologically, this research is classified as a bibliographical study for the identification and analysis on the dichotomy between (a) criticality and criticality, the transition from common sense to critical thinking and the elucidation of critical sense in the educational process. It is certified in this study the importance of interaction and interrelation of learning and the function of the teacher, for the manifestation of critical thinking of students, in which educators have strategic and decisive role in the insertion of themes that encompass the political, social, cultural, environmental dimensions among others, qualifying students for a critical positioning in the face of the dilemmas of relations between man, society and nature, having as horizon processes of humanization and social transformation in the formation for citizenship in its most comprehensive meaning.